External financing, technological changes, and employees - Kim, E Han; Li, Yuan; Lu, Yao; Shi, Xinzheng (Review of Finance, 2024)
Abstract Using exogenous shocks on the ability to issue seasoned equity offerings (SEOs), we show SEOs lead to a higher employee skill composition, that is, a lower (higher) proportion of low (high) skilled workers. The decrease in low-skilled workers exceeds the increase in high-skilled workers, resulting in reduced employment at the firm level. These effects are more significant when firms invest more in technology following SEOs and face greater financial constraints before SEOs, suggesting that SEOs relieve budget constraints on technology investments. These findings demonstrate that while external equity financing helps upgrade technology to improve productivity, it has a dark side for low-skilled workers.